96=-8(n-7)

Simple and best practice solution for 96=-8(n-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 96=-8(n-7) equation:


Simplifying
96 = -8(n + -7)

Reorder the terms:
96 = -8(-7 + n)
96 = (-7 * -8 + n * -8)
96 = (56 + -8n)

Solving
96 = 56 + -8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8n' to each side of the equation.
96 + 8n = 56 + -8n + 8n

Combine like terms: -8n + 8n = 0
96 + 8n = 56 + 0
96 + 8n = 56

Add '-96' to each side of the equation.
96 + -96 + 8n = 56 + -96

Combine like terms: 96 + -96 = 0
0 + 8n = 56 + -96
8n = 56 + -96

Combine like terms: 56 + -96 = -40
8n = -40

Divide each side by '8'.
n = -5

Simplifying
n = -5

See similar equations:

| -3x-2(9+5x)=13-3(2x-3) | | 3(3w-2)=2(3w+3) | | 3(-7-7b)=-189 | | 2z-13=-8z+27 | | 6(1-8a)+7(3a+8)=-73 | | 2x+40=x+2y | | 15/100=23/x | | (4y+8)-(4+3y)=8 | | 4x^2-10x+7=0 | | 6a^2-3a+a-2a^2= | | 9y+27=-72 | | -x/2+3=-12 | | 92=6(r+2)+4r | | 3y-1/2=z | | 90=6(3x+1)-6x | | 5x-12+3x+6=72 | | -40+8=-10+-24 | | 4x^6-3y^4+6x^6+6y^4= | | -2=5+1x | | x/3-9=10 | | 2t+3+3t-4t=4+2 | | 4x^6-3y^4+6x^6y^4-6x^6+6y^4= | | -x-2=6 | | x/2-13=11 | | -53+29=x | | x^2+16=-5 | | -53+23=x | | -53+=x | | 5x^2+5y^2=25 | | a=36-cforb | | 3x+12=-18x-9x+1 | | -53+29= |

Equations solver categories